Big data and firm greenwashing: evidence from China’s national big data comprehensive pilot zone - Jianjun Sun; Nannan Zu; Chao Zhang (Humanities & Social Sciences Communications)
Abstract Big data is playing an increasingly important role in addressing environmental challenges. Using the launch of China’s national big data comprehensive pilot zone in 2016 as an exogenous event, this paper employs the difference-in-differences method to examine the causal effect of big data on firm greenwashing. The regression result indicates that big data has an inhibitory effect on firm greenwashing. A plausible underlying mechanism is that big data enhances environmental performance and alleviates information asymmetry between the firm and stakeholders. The inhibitory effect is more pronounced in state-owned enterprises and those with high market competition. The findings better explain how the digital factor drives green development at the firm level.